National Cancer Institute Centers and Society of Surgical Oncology Cancer Research Synergy - Kim, Bradford J. (J Surg Res, 2018)
BACKGROUND: The objective of this study was to examine the influence of Surgical Society Oncology (SSO) membership and National Cancer Institute (NCI) status on the academic output of surgical faculty. METHODS: NCI cancer program status for each department of surgery was identified with publically available data, whereas SSO membership was determined for every faculty member. Academic output measures such as NIH funding, publications, and citations were analyzed in subsets by the type of cancer center (NCI comprehensive cancer center [CCC]; NCI cancer center [NCICC]; and non-NCI center) and SSO membership status. RESULTS: Of the surgical faculty, 2537 surgeons (61.9%) were from CCC, whereas 854 (20.8%) were from NCICC. At the CCC, 22.7% of surgeons had a history of or current NIH funding, compared with 15.8% at the NCICC and 11.8% at the non-NCI centers. The academic output of SSO members was higher at NCICC (52 ± 113 publications/1266 ± 3830 citations) and CCC (53 ± 92/1295 ± 4001) compared with nonmembers (NCICC: 26 ± 78/437 ± 2109; CCC: 37 ± 91/670 ± 3260), respectively, P < 0.05. Multivariate logistic regression revealed that SSO membership imparts an additional 22 publications and 270 citations, whereas NCI-designated CCC added 10 additional publications, but not citations. CONCLUSIONS: CCCs have significantly higher academic output and NIH funding. Recruitment of SSO members, a focus on higher performing divisions, and NIH funding are factors that non-NCI cancer centers may be able to focus on to improve academic productivity to aid in obtaining NCI designation.